Wybrane elementy kierowania oraz edukacji muzycznej a rozwój dziecka = Guidance and music education in child`s development - Golema, Amelia (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
In Edwin Gordon`s music learning theory, the most critical period in every individual`s musical life is from birth to age five. Guidance and music education provided by parents and music teachers have a great influence on child`s development, not only in a music area. Singing, playng instruments and improvising can develop child`s personality and creative thinking.
Keywords: rozwój muzyczny; edukacja muzyczna; teoria uczenia się muzyki Edwina Gordona; musical progress; Edwin Gordon`s music learning theory; music education